Effect of modified polyvinyl alcohol on fluidity of cement slurry. Issue 1 (September 2021) - Zhang, Jian; Li, Zhihong; Tang, Kai; Shi, Ya; Du, Weichao
Abstract: Select appropriate amount of dispersant to modify polyvinyl alcohol, and explore the influence of modified polyvinyl alcohol on the rheology of cement slurry by investigating the thickening time, initial consistency, free liquid and density, fluidity index and viscosity coefficient of cement slurry. The results show that the thickening time of cement slurry is the shortest when the dispersant parameter is 1.5%, and the rheology of cement slurry becomes better and better when the dosage of polyvinyl alcohol increases. When 1.5% polyvinyl alcohol is added, the rheology of cement slurry is good and the viscosity is low.